Fall of non-spherical particles through a power law fluid - Machač, Ivan; Lecjaks, Zdeněk; Šiška, Bedřich (Univerzita Pardubice, 2000)
The free fall of cylinders and rectangular prism through pseudoplastic and elastic polymer solutions has been investigated experimentally in creeping flow regime. The terminal falling velocities were measured in perspex cylindrical test columns. The influence of rheological properties of fluid and wall effects on the particle terminal falling velocity model have been proposed for prediction of the wall effect correction factor and for prediction of the terminal falling velocity of short cylinders and prisms.
Keywords: chemické inženýrství; fyzika kapalin; kinetika; reologické vlastnosti; polymerní roztoky